IMPLEMENTASI ASESMEN DALAM KURIKULUM MERDEKA DI PENDIDIKAN ANAK USIA DINI - Berliana, Dinda; Atikah, Cucu (Jurnal Citra Pendidikan, 2024)
This study aims to find out the concept and implementation of assessment in the independent curriculum in Early Childhood Education. The research method used in this research is a type of qualitative research through literature study. The results and discussion of this study are that the assessment of the independent curriculum consists of two types, namely formative assessment and summative assessment. Formative assessment is carried out at the beginning of the activity and during the learning process. Formative assessment aims to monitor and improve the learning process, as well as evaluate the achievement of learning objectives. Summative assessment is conducted at the end of the learning activity. Formative assessment in the foundation phase can be conducted over one or two weeks. Learning assessment in Early Childhood Education refers to authentic assessment, which is an assessment that is in accordance with the actual situation. The implementation of assessment in Early Childhood Education uses four assessment techniques, namely checklist assessment, anecdotal notes, work assesment and serialized photos.